CO2 high temperature heat pump – a promising solution. Issue 1 (December 2020) - Talaba, O; Dima, D; Buiuc, V; Ionita, C; Stefanescu, M F; Serban, A; Dobrovicescu, A
Abstract: The study focuses on obtaining hot water above 80°C for industrial purposes. Compared to the electrical heating the use of a heat pump appears much more efficient. A comparative analysis using different refrigerants is carried out. The cold source is waste heat from an industrial process. The exergetic analysis reveals the advantages and weaknesses of using CO2 as refrigerant. Based on the exergy destruction concept several schematics of two-stage CO2 Heat Pumps are considered. For high temperature water heating, a CO2 Heat Pump system represents a promising solution.